Influence of initial defect density on mechanical properties of AISI H13 hot-work tool steel produced by laser powder bed fusion and hot isostatic pressing. (1st January 2022) - Kunz, Johannes; Herzog, Simone; Kaletsch, Anke; Broeckmann, Christoph
ABSTRACT: In this study, the microstructure and mechanical properties of martensitic hot-work tool steel AISI H13 produced by laser powder bed fusion (LPBF) under argon atmosphere in different LPBF process times were analysed in the as-built, hardened and tempered (HT) and hot isostatic pressed, hardened and tempered (HIP+HT) condition and compared to conventionally manufactured reference material. Three parameter sets were selected to adjust an initial defect density of 0.6%, 0.9% and 2.2% and thus process time reductions of 17% and 29%. We observed a change in the defect type from almost argon-free microcracks to argon-filled pores with higher scan velocities. Argon embrittlement was evident also in the results of tensile, notched impact toughness and fatigue tests. After HIP+HT a fatigue strength of 972 MPa was obtained for the set with 0.6% microcracks, but only 775 MPa and 718 MPa were obtained for samples with argon porosity.